ANALISIS IMPLEMENTASI SOFTWARE AS A SERVICE PADA INDUSTRI PERHOTELAN DAERAH BALI - Ardini, I Gusti Ayu Ari; Masakazu, Kadek (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2020)
Software as a Service (SaaS) is a solution for small and medium enterprise that want to implement information system without having to prepare a complex infrastructure so as to minimize costs. This research aims to find out the factors that influence implementation SaaS based on three indicators, relative advantage, compatibility, and complexity in Baliâ€™s hotel industry. This research uses a simple random sampling technique and data collected using a questionnaire and then analyzed using multiple linier regression test. The results of this study indicated that all of variable, relative advantage, compatibility and complexity together affect the implantation of SaaS. Then, if analyzed partially using T test, was found that relative advantage and complexities variable had most significant effect on SaaS implementation in Hotel Industry, the result show the significance value was below 0,05. So, the both of variable were the predictors in the process of SaaS implementationÂ